Associations of cognition with physical functioning and health-related quality of life among COPD patients. (May 2016) - Schure, Mark B.; Borson, Soo; Nguyen, Huong Q.; Trittschuh, Emily H.; Thielke, Stephen M.; Pike, Kenneth C.; Adams, Sandra G.; Fan, Vincent S.
Abstract: Background: Neurocognitive impairment has been described in COPD patients, but little is known about its relationship with physical functioning and health-related quality of life (HRQL) in this chronically ill patient group. Methods: 301 stable COPD patients completed the Trail Making Test (TMT-A: psychomotor speed and TMT-B: executive control); 198 patients completed the Memory Impairment Screen (MIS). Standardization of TMT-A and TMT-B scores to a normative population yielded classifications of normal, borderline, or impaired cognitive status. Using multivariable regression, we examined the relationship between the TMT-A, TMT-B, and MIS with physical functioning (physical activity, 6-min walk test, and grip strength) and health-related quality of life (HRQL) measured with the Chronic Respiratory Questionnaire and the SF-36. Results: Nearly 30% of patients had either borderline or impaired cognition on the TMT-A or TMT-B. Adjusted models indicated that those with either borderline or impaired cognitive functioning had weaker grip strength (TMT-A borderline: β  = −2.9, P  < 0.05; TMT-B borderline: β  = −3.0, P  < 0.05; TMT-B impaired: β  = −2.5, P < 0.05) and lower scores on the mental health component summary score (MCS-SF-36 HRQOL) measure (TMT-A impaired: β  = −4.7, P  < 0.01). No adjusted significant associations were found for other physical functioning measures or the other HRQL measures. Impaired memory showed a significant association only with the MCS scale. Conclusions: Cognitive function was not associated with most standard indicators of physical function or most measures of HRQL in COPD patients. Both TMT-A and TMT-B were associated with weaker grip strength, and the TMT-A and MIS with poorer mental health. Highlights: Approximately 30% of COPD patients had either borderline or impaired cognition. Those with borderline or impaired cognitive functioning had weaker grip strength. Those with borderline or impaired cognitive functioning had poorer mental health. No significant associations were found for other physical functioning measures. No significant associations were found for health-related quality of life.